Validation of the Bullying Scale for Adults - Results of the PRONIA-study. (October 2020) - Haidl, Theresa Katharina; Schneider, Nicole; Dickmann, Kim; Ruhrmann, Stephan; Kaiser, Nathalie; Rosen, Marlene; Seves, Mauro; Lichtenstein, Thorsten; Upthegrove, Rachel; Salokangas, Raimo K.R.; Pantelis, Christos; Meisenzahl, Eva; et al.
Abstract: Background: Bullying as a specific subtype of adverse life events is a major risk factor for poor mental health. Although many questionnaires on bullying are available, so far none covers bullying retrospectively throughout school and working life. To close this gap, the Bullying Scale for Adults (BSA) was designed. Methods: Based on data of 622 participants from five European countries collected in the prospective multicenter Personalized Prognostic Tools for Early Psychosis Management (PRONIA) study, we investigated whether the BSA is a reliable and valid measurement for bullying and whether there is a difference across different diagnostic groups of early mental disorders (recent onset depressive/ psychotic patients, patients at clinical high-risk of psychosis) and healthy controls. Results: Bullying experiences were significantly less frequent in healthy controls than in patient groups, with no significant differences between the three clinical groups. The BSA exhibited a high item scale discrimination (r > .3) and very good internal consistency (Cronbach's α = .93). Four factors were identified: 1. Sexual harassment, 2. Emotional Abuse, 3. Physical Abuse, 4. Problems at school. The highly significant correlation between bullying, and childhood adversities and trauma (r = .645, p < .001) indicated good concurrent validity. Discussion: The BSA is the first validated questionnaire that, in retrospective, reliably records various aspects of bullying (incl. its consequences) not only throughout childhood but also working life. It can be used to assess bullying as a transdiagnostic risk factor of mental disorders in different mental disorders, esp. psychosis and depression. Highlights: BSA assesses bullying retrospectively throughout school and working life. Bullying was significantly less frequent in healthy controls than in patients. No differences between patient groups regarding bullying. High item scale discrimination and very good internal consistency. Good concurrent validity.